1989
DOI: 10.1002/rcm.1290031105
|View full text |Cite
|
Sign up to set email alerts
|

Effect of trifluoroacetic acid on the reduction of disulfide bridges in peptides analyzed by fast‐atom bombardment mass spectrometry

Abstract: Some of the factors that influence the reduction of disulfide-containing peptides under fast-atom bombardment have been investigated using two neurohormonal peptides that include disulfide bridges in their structures. Deaminoarginine-vasopressin (DAVP) and arginine-vasopressin (AVP) have been analyzed as their acetate and trifluoroacetate salts. Results obtained in a thioglycerol matrix indicate that the peptides analyzed as their acetate salts are completely reduced under bombardment, whereas the trifluoroace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…and Back , will take two average values, thus minimizing the errors on background assessment and on the values of redox processes. The ion intensities measured in the molecular ion region can be simulated according to eqs [11][12][13][14][15][16][17][18], which include all of the variables of interest. It is the I k values, which include the contributions from background, natural isotopic abundances, and the oxidized/reduced species accordingly, that the program tries to best match with observed peak inten-sities, The model uses eqs 12-17 to estimate values for the processes and eqs 11-18 to optimize them.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…and Back , will take two average values, thus minimizing the errors on background assessment and on the values of redox processes. The ion intensities measured in the molecular ion region can be simulated according to eqs [11][12][13][14][15][16][17][18], which include all of the variables of interest. It is the I k values, which include the contributions from background, natural isotopic abundances, and the oxidized/reduced species accordingly, that the program tries to best match with observed peak inten-sities, The model uses eqs 12-17 to estimate values for the processes and eqs 11-18 to optimize them.…”
Section: Methodsmentioning
confidence: 99%
“…Instrumental parameters associated with the FAB/LSIMS source conditions may also play an im-portant role in determining the extent of reduction observed. Those parameters that have been studied include time of irradiation [8,14,16,17,23]; primary beam energy [15,20,28); and bombarding beam density (flux) [12,15,20,23,28]. Wirth et al [8] observed a time dependence in their FAB analysis (Xe O primary beam) of azo-group-eontaining peptides.…”
mentioning
confidence: 99%
“…We, however, have not observed a difference in nanoparticle structure when PEG-S-POD was equilibrated in either buffer (data not shown). However, TFA has been found to inhibit reduction of disulfide bonds 22 . To determine whether the use of either TFA or AmAc as a counterion for equilibration of PEG-SS-POD could inhibit reduction of the disulfide bond, we incubated PEG-SS-POD equilibrated in each buffer with β-mercaptoethanol (Figure 1D).…”
Section: Resultsmentioning
confidence: 99%
“…Addition of trifluoroacetic acid (TFA) to glycerol-thioglycerol matrix mixture also assists in maintaining the integrity of the disulfide bond. 27 In 1987, we reported in detail the FAB-induced fragmentation behavior of several C-terminal-extended enkephalins using glycerol as the matrix." The foremost process of sequence ion formation in the positive-ion FAB was fission of the amino-alkyl bond of the peptide backbone to yield z-type C-terminal sequence ions.…”
Section: Introductionmentioning
confidence: 99%